1987
DOI: 10.1111/j.1476-5381.1987.tb08968.x
|View full text |Cite
|
Sign up to set email alerts
|

P2‐purinoceptors of two subtypes in the rabbit mesenteric artery: reactive blue 2 selectively inhibits responses mediated via the P2y‐ but not the P2x‐purinoceptor

Abstract: I mc-Methylene ATP and ATP both produced concentration-dependent contractions of the isolated mesenteric artery of the rabbit that were not inhibited by reactive blue 2. 2 In preparations where the tone had been raised with noradrenaline, ATP and 2-methylthio ATP, but not a,-methylene ATP, produced relaxations of the vessel. These relaxations were inhibited in the presence of reactive blue 2. 3 Reactive blue 2 did not inhibit the contractions to noradrenaline, and only slightly inhibited relaxations to adenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
2

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(159 citation statements)
references
References 28 publications
11
146
2
Order By: Relevance
“…The ATP-induced phospholipid release by cultured type II pneumocytes was blocked by reactive blue 2 in a dose-dependent manner (Rice & Singleton, 1989). Reactive blue 2 was previously found to be a specific P2y receptor blocker in smooth muscle preparations (Burnstock & Warland, 1987). In the present HTSE cell culture system, the concentrations of reactive blue 2 which caused phospholipid release in type II pneumocytes did not block the ATP-induced mucin release, but rather increased mucin release by itself (Figure 4).…”
Section: Discussionmentioning
confidence: 48%
“…The ATP-induced phospholipid release by cultured type II pneumocytes was blocked by reactive blue 2 in a dose-dependent manner (Rice & Singleton, 1989). Reactive blue 2 was previously found to be a specific P2y receptor blocker in smooth muscle preparations (Burnstock & Warland, 1987). In the present HTSE cell culture system, the concentrations of reactive blue 2 which caused phospholipid release in type II pneumocytes did not block the ATP-induced mucin release, but rather increased mucin release by itself (Figure 4).…”
Section: Discussionmentioning
confidence: 48%
“…These results indicate that there is a regional difference in the ATP response of dog cerebral arteries (Muramatsu et al, 1980). Recently, P2-purinoceptors have been subdivided into P2, and P2y, which are selectively inhibited by x,p-methylene ATP and reactive blue 2, respectively (Burnstock & Kennedy, 1985;Burnstock & Warland, 1987b;Hopwood & Burnstock, 1987). The contraction induced by ATP of the dog basilar artery was abolished by desensitization to x,B-methylene ATP, thereby suggesting that the contractile response, at least, is mediated through the P2h-purinoceptor.…”
Section: Methodsmentioning
confidence: 95%
“…On the other hand, the relaxant response to ATP was not attenuated by x,-methylene ATP although the pattern of the response was modified. This lack of inhibition may mean that the relaxation induced by exogenous ATP is predominantly mediated through different types of purinoceptors such as P2, or P, (Burnstock & Warland, 1987b). Previously we observed that ATP-induced relaxation of the dog cerebral artery was partially but not completely inhibited by a PI-purinoceptor antagonist, theophylline (Muramatsu et al, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…or 95% confidence interval (in parenthesis). EC 50 , EC 40 and EC 20 represent the molar concentration of the agonist nedded to cause 50%, 40% and 20% of the maximum response, respectively; pEC 50 , pEC 40 and pEC 20 are the negative logarithme to base 10 of the EC 50 , EC 40 and EC 20 of an agonist, respectively; pA 2 is the negative logarithme to base 10 of the molar concentration of the antagonist that makes it necessary to double the concentration of the agonist nedded to elicit the original response.…”
Section: Adenosine Receptors In the Splanchnic Circulationmentioning
confidence: 99%
“…ATP elicits arterial contraction through stimulation of P2X receptors in the mesenteric artery of the rat [54, 73,85,123,137], guinea-pig [116] and rabbit [20], and in the rat hepatic artery [130] and the guinea-pig portal vein [125]. The P2X 1 subtype is the receptor responsible for the purine nucleotides-induced arterial contractions [54,177].…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 99%